PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PENGHINDARAN PAJAK DI LQ45 TAHUN 2020-2021 - SONYA DEVITA SARI LUMBAN TOBING; REMISTA SIMBOLON (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2023)
This study aims to examine the effect of profitability, leverage, CSR, and tax avoidance on LQ45 2020-2021. The data source in this study is additional information from bank records regarding the LQ45 business index purchased on the IDX. The data collection method was carried out using the analytical method, using secondary data and will be processed using SPSS 25. The data analysis technique used is descriptive statistical test, classical assumption test, hypothesis testing, and multiple regression analysis with the help of SPSS for windows version 25. Results This study shows that the profitability variable has a positive and significant effect on tax avoidance, the leverage variable has a positive and significant effect on tax avoidance, and the Corporate Social Responsibility (CSR) variable shows that the Corporate Social Responsibility variable has a positive and significant effect on tax avoidance. Based on the simultaneous test or F test conducted, it shows that the variables of profitability, leverage and CSR have a simultaneous or joint effect on tax evasion in LQ45.